A case of systemic lupus erythematosis with secondary APLA in a male - Brunda, M S; Dharmapalaiah, Chethana; Subramanian, Maheswaran (Indian Journal of Case Reports, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease in which organs and cells undergo damage initially mediated by tissue-binding autoantibodies and immune complexes. Ninety percent of patients are women of childbearing years; people of all genders, ages, and ethnic groups are susceptible. Here is the case of 51 years male diagnosed with SLE with secondary antiphospholipid syndrome (antiphospholipid antibodie) and lupus nephritis confirmed by renal biopsy. The patient presented with vasculitic rash with proteinuria. Laboratory evaluation showed antinuclear antibody by immunofluorescence 3+, elevated activated partial thromboplastin time anti-cardiolipin antibody immunoglobulin G and lupus anticoagulant with dilute Russell viper venom time were positive. Renal biopsy showed International Society of Nephrology/Renal Pathology Society classification class III (A)+V nephritis. He was managed with low-dose glucocorticoid, oral vitamin K antagonist, and mycophenolate mofetil. The patient had a good clinical response.